An Analysis of Verbal Humor in Ini Talk Show - Fitri Nurul Azka; Hamzah Hamzah (Universitas Negeri Padang, 2019)
One of the ways to express the idea or opinion in communication is through humor. It is not only to express the idea, humor also can be functioned to entertain, one of them through television program, talk show. This research aimed to compare the types of verbal humor that found in Ini Talk Show. This research was descriptive comparative. The data were the clauses which consist of verbal humor within transcribed video. The total of video were 5 videos. The data were analyzed by using theory of Shade (1996) and General Theory of Verbal Humor (1991). Theory of Shade (1996) was used to analyze the types of verbal humor and General Theory of Verbal Humor (1991) used to analyze the types of verbal humor that found in both object. The result of the research showed that there were 192 numbers of verbal humor found in Ini Talk Show. It is found that 10 out of 12 types of verbal humor found in Ini Talk Show. It means, the hosts of the show were good in creating humorous situation in the show.